2019
DOI: 10.1002/eqe.3230
|View full text |Cite
|
Sign up to set email alerts
|

Nonsymmetrical loading protocols for shear links in eccentrically braced frames

Abstract: The AISC Seismic Provisions for Structural Steel Buildings (AISC 341-16) provide a testing protocol for qualification of link-to-column connections in eccentrically braced frames (EBFs). This symmetrical testing protocol was developed by conducting nonlinear time history analysis on representative EBFs designed according to the International Building Code. Although the testing protocol is intended for qualification of link-to-column connections, many research programs have employed this recommended protocol fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…Çalışma kapsamında bağ kirişi maksimum kesme kuvveti dayanımının bağ kirişi karakteristik kesme kuvveti dayanımına oranı pekleşme katsayısı olarak dikkate alınmıştır. Bağ kirişlerinin gerekli dönme kapasitelerinden daha yüksek dönme kapasitesine ulaşabildikleri durumlar bulunmaktadır [36]. Ancak bağ kirişlerinin hedef dönme değerlerinin altında veya bu değerlere yakın dönme kapasitelerine sahip olduğu durumlar da raporlanmıştır [8, 20,37].…”
Section: Değerlendirme Ve Tartışma (Evaluation and Discussion)unclassified
“…Çalışma kapsamında bağ kirişi maksimum kesme kuvveti dayanımının bağ kirişi karakteristik kesme kuvveti dayanımına oranı pekleşme katsayısı olarak dikkate alınmıştır. Bağ kirişlerinin gerekli dönme kapasitelerinden daha yüksek dönme kapasitesine ulaşabildikleri durumlar bulunmaktadır [36]. Ancak bağ kirişlerinin hedef dönme değerlerinin altında veya bu değerlere yakın dönme kapasitelerine sahip olduğu durumlar da raporlanmıştır [8, 20,37].…”
Section: Değerlendirme Ve Tartışma (Evaluation and Discussion)unclassified
“…The far-field ground motion set of FEMA P695 5 was used in a number of studies on the response of EBF buildings. [6][7][8] These ground motions were scaled to MCE level or above MCE level with different probabilities of collapse. Kuşyılmaz and Topkaya 6 performed a numerical study on six EBF archetypes designed with current response factors and reported that median LRAs can be as much as 0.23 rad when these archetypes are subjected to ground motions scaled according to 20% probability of collapse at MCE (i.e., 1.09 to 1.15 times MCE).…”
Section: Noveltymentioning
confidence: 99%
“…The same value increased to 0.38 rad if the deformations of other members were neglected. The far‐field ground motion set of FEMA P695 5 was used in a number of studies on the response of EBF buildings 6–8 . These ground motions were scaled to MCE level or above MCE level with different probabilities of collapse.…”
Section: Introductionmentioning
confidence: 99%
“…Al-Janabi et al [5] carried out nonlinear time-history analyses to investigate the median link rotation angle demands and then, develop loading protocols for short links of eccentrically braced frames (EBF). The results indicated the single-sided nature of link rotation histories and the need to develop asymmetrical loading protocols.…”
Section: Introductionmentioning
confidence: 99%
“…Suzuki et al [6] proposed a methodology to construct a set of loading protocols which combines the asymmetric lateral loading and varying axial loading as near-collapse protocol for hollow square steel (HSS) columns. Accordingly to Al-Janabi et al [5], they have pointed out that the conventional symmetric loading protocols provide an overall conservative estimation of the seismic demands in individual structural components.…”
Section: Introductionmentioning
confidence: 99%